Impact of remuneration on guideline adherence: Empirical evidence in general practice. (March 2013) - van Dijk, Christel E.; Verheij, Robert A.; Spreeuwenberg, P.; van den Berg, Michael J.; Groenewegen, Peter P.; Braspenning, Jozé; de Bakker, Dinny H.
Abstract Background and objective. Changes in the Dutch GP remuneration system provided the opportunity to study the effects of changes in financial incentives on the quality of care. Separate remuneration systems for publicly insured patients (capitation) and privately insured patients (fee-for-service) were replaced by a combined system of capitation and fee-for-service for all in 2006. The effects of these changes on the quality of care in terms of guideline adherence were investigated. Design and setting. A longitudinal study from 2002 to 2009 using data from patient electronic medical records in general practice. A multilevel (patient and practice) approach was applied to study the effect of changes in the remuneration system on guideline adherence. Subjects. 21 421 to 39 828 patients from 32 to 52 general practices (dynamic panel of GPs). Main outcome measures. Sixteen guideline adherence indicators on prescriptions and referrals for acute and chronic conditions. Results. Guideline adherence increased between 2002 and 2008 by 7% for (formerly) publicly insured patients and 10% for (formerly) privately insured patients. In general, no significant differences in the trends for guideline adherence were found between privately and publicly insured patients, indicating the absence of an effect of the remuneration system on guideline adherence. Adherence to guidelines involving more time investment in terms of follow-up contacts was affected by changes in the remuneration system. For publicly insured patients, GPs showed a higher trend for guideline adherence for guidelines involving more time investment in terms of follow-up contacts compared with privately insured patients. Conclusion. The change in the remuneration system had a limited impact on guideline adherence.